Bioactive Compounds of Chamber-Dried Blueberries at Controlled Temperature and Wines Obtained from Them - Juan Martin-Gomez; M. Angeles Varo; Julieta Merida; Maria P. Serratosa (Journal of Chemistry)
The effects of chamber drying under controlled temperature and moisture conditions and fermentation process on blueberry juices to obtain three wines were studied in this work. Drying was carried out with a view to increase the sugar content and obtain wines with an ethanol content similar to a commercial grape wine or to obtain sweet wines. Analyses included color parameters; browning index; and anthocyanin, flavonols, flavan-3-ol derivatives, and tannin concentrations, as well as vitamin C concentration and antioxidant activity. Based on the results, drying increases color and the concentration of anthocyanins and tannins most probably by the effect of dehydration of the berries and diffusion of the colored compounds from the skin to the pulp due to the structural alterations in their skin. In addition, drying decreases flavonols, flavan-3-ol derivatives, and vitamin C concentrations. The browning index, anthocyanins, and tannins decreased with the fermentation time, and vitamin C was constant with the fermentation time. The sensory analysis showed that the wines with the best sensory characteristics were those with residual sugar, partial fermented wines 1 and 2.